Editorial Special Issue: Rail Freight Interoperability in Europe: Lessons from the Reorient Project - Tavasszy, Lóri (European Journal of Transport and Infrastructure Research, 2009)
The outlook of a liberalised rail freight sector, which functions in a seamless way throughout Europe, is a promising one. A market which is open for competition for rail freight services will allow transportation to become faster, cheaper and more reliable, to the benefit of the EU economies. Moreover, it will strengthen the railways’ competitive position compared to road transport – another strategic objective of the EU transport policy. The task of re-organisation is a complex one however, as market liberalisation and international harmonisation processes interact. On the one hand, as rail only competes well with road transport over longer distances, the view towards liberalisation needs to be a truly international one. For the EU member states, this creates a dilemma: stimulate transport demand by actively promoting the development of internationally competing services, or protect domestic sectoral interests by passively resisting a competitive market? Fact is, the European railways system still struggles with very fragmented physical and management structures, due to national borders, rules and standards. In other words, national systems are not “interoperable”. If we want to be able to handle the expected growth of European freight flows, improvements in the European rail freight system, including its governance and management, are needed. This is the field of research we focus on in this special issue.